2015
DOI: 10.1038/nature14177
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of body mass index yield new insights for obesity biology

Abstract: Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10−8), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

151
4,364
22
60

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 4,048 publications
(4,683 citation statements)
references
References 75 publications
151
4,364
22
60
Order By: Relevance
“…Therefore, we further investigated the causal effect of BMI on PAI‐1 levels using 77 genome‐wide significant loci identified in a large BMI GWAS in European populations (Data S1). 36 This result shows that BMI has a causal effect on PAI‐1 in the positive direction (β: 0.21; 95% CI: 0.13, 0.29; Table S3), and was consistent with sensitivity analyses using a median estimator approach and MR‐Egger regression to test for potential pleiotropic effects.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, we further investigated the causal effect of BMI on PAI‐1 levels using 77 genome‐wide significant loci identified in a large BMI GWAS in European populations (Data S1). 36 This result shows that BMI has a causal effect on PAI‐1 in the positive direction (β: 0.21; 95% CI: 0.13, 0.29; Table S3), and was consistent with sensitivity analyses using a median estimator approach and MR‐Egger regression to test for potential pleiotropic effects.…”
Section: Resultssupporting
confidence: 80%
“…Thus, we considered the MR analyses viable and obtained summary statistics for circulating PAI‐1 levels, CHD and CHD risk factors from previous GWASs as listed in Table 1. These are based on the largest GWAS meta‐analysis for each phenotype at the time of analysis and primarily conducted on European ancestry samples 28, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42…”
Section: Methodsmentioning
confidence: 99%
“…Although it has become a common approach for the analysis of GWAS data, 25 there are reservations about the impact of INT on the results from association testing. 24 Both Beasley et al 24 and Buzkova 26 investigated the effect of INT when there is heteroskedasticity and demonstrated that Type I error was not well-controlled.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded one known locus, in GCKR, owing to its known pleotropic effect on multiple human complex traits [14]. In addition, we constructed a GRS for circulating BCAA levels with and without the PPMK1 single nucleotide polymorphism (SNP) rs9637599 and performed analysis considering the association of rs9637599 with BMI (p = 0.035) [15] and obesity class I (p = 0.00042) [16] in the publicly available GWAS summary data.…”
Section: Measurement Of Insulin Resistancementioning
confidence: 99%